Post cyclone rehabilitation of agriculture in the Sidr affected areas in South West Bangladesh - Biswas, Ratan Chandra (BRAC University, 2012)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2011.